Відповідь:
(-∞; 0]
Покрокове пояснення:
№ 18
x≤0
№ 17
cos(3π-2x)=
cos3π*cos2x+sin3π*sin2x=
-1*cos2x+0*sin2x=
-cos2x=
-()=
--=0
-+
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Відповідь:
(-∞; 0]
Покрокове пояснення:
№ 18
x≤0
№ 17
cos(3π-2x)=![sin^{2} x sin^{2} x](https://tex.z-dn.net/?f=sin%5E%7B2%7D%20x)
cos3π*cos2x+sin3π*sin2x=![sin^{2} x sin^{2} x](https://tex.z-dn.net/?f=sin%5E%7B2%7D%20x)
-1*cos2x+0*sin2x=![sin^{2} x sin^{2} x](https://tex.z-dn.net/?f=sin%5E%7B2%7D%20x)
-cos2x=![sin^{2} x sin^{2} x](https://tex.z-dn.net/?f=sin%5E%7B2%7D%20x)
-(
)=![sin^{2} x sin^{2} x](https://tex.z-dn.net/?f=sin%5E%7B2%7D%20x)
-
-
=0
-
+